Revolutionizing Mobile Broadband: Assessing Multicellular Networks in Indoor and Outdoor Environments - Alhammadi, Abdulraqeb; Al-Alawi, Rajaa Mohammed; Majan Abdullah Al Jahdhami; El-Saleh, Ayman A.; Ismail, Zool Hilmi; Shamsan, Zaid Ahmed; Shayea, Ibraheem (Institute of Electrical and Electronics Engineers (IEEE), 2024)
The exponential surge in mobile device usage has propelled a steep rise in mobile data demand, particularly with the advent of 5G networks aiming to cater to this burgeoning need. Ensuring top-notch quality of service (QoS) is pivotal in deploying such advanced wireless technologies without compromising base station throughput. Continuous enhancements in established cellular networks like 3G, 4G, and emerging 5G networks remain imperative to uphold satisfactory network performance. This paper comprehensively analyzes 5G network performance across indoor and outdoor environments in Muscat, Oman. The study involved walk tests within three indoor locations and drive tests outdoors, using devices from three mobile providers: Omantel, Ooredoo, and Vodafone. Metrics such as signal quality, data rate, ping, and serving time were assessed. Results indicated the dominance of 4G networks indoors and 5G outdoors across all providers. In the outdoor scenario, the observed data rate for the 5G network did not meet anticipated levels, potentially due to handover issues or other factors affecting signal continuity. Moreover, the measurement data collected within indoor scenarios indicates that approximately 80% of the recorded data stems from 4G networks. As a consequence, this disproportionate reliance on 4G is likely influencing network performance, possibly leading to decreased data rates. While 5G showcased incremental improvements over 4G in some instances, it is still in its nascent phase. Recommendations include continuous network monitoring by operators and augmented 5G base station deployment to heighten QoS by ensuring higher data rates and minimal latency across both indoor and outdoor settings.
Keywords: drive test; cellular networks; QoS; QoE; Electrical engineering. Electronics. Nuclear engineering; Mobile broadband; data rate; TK1-9971